(untitled) (Global Journal of Science Frontier Research, 2015)
The drivers of community structure, diversity and distribution, has generated a lot of interest among many scientists, giving the complex environmental and biological interaction, at different scales. This prompted the application of multivariate techniques to explain the factors influencing variations in wetland plant community structure, diversity and distribution, in Northern Region of Ghana. A total of 40 species were sampled and separated into four community structure(swamp forest community; shrub land community; grassland community and herbaceous community), using DCA. Herbs, grasses and trees/shrubs constituted 72.72%, 27.27% and 0.01% respectively. Change in plant community distribution was marginal, as the first two axes only explained 1.18% of the variance along a longitudinal profile of environmental gradient. Species turnover was low, indicating a far more unimodal responses of some species to a gradient of disturbances than others. Plant diversity was moderate(H′ = 1.86 -2.66).